Effect of Acetazolamide and Zoledronate on Simulated High Altitude-Induced Bone Loss - Brent, Mikkel Bo; Simonsen, Ulf; Thomsen, Jesper Skovhus; Brüel, Annemarie (Frontiers in Endocrinology, 2022)
Exposure to hypobaric hypoxia at high altitude puts mountaineers at risk of acute mountain sickness. The carbonic anhydrase inhibitor acetazolamide is used to accelerate acclimatization, when it is not feasible to make a controlled and slow ascend. Studies in rodents have suggested that exposure to hypobaric hypoxia deteriorates bone integrity and reduces bone strength. The study investigated the effect of treatment with acetazolamide and the bisphosphonate, zoledronate, on the skeletal effects of exposure to hypobaric hypoxia. Eighty 16-week-old female RjOrl:SWISS mice were divided into five groups: 1. Baseline; 2. Normobaric; 3. Hypobaric hypoxia; 4. Hypobaric hypoxia + acetazolamide, and 5. Hypobaric hypoxia + zoledronate. Acetazolamide was administered in the drinking water (62 mg/kg/day) for four weeks, and zoledronate (100 μg/kg) was administered as a single subcutaneous injection at study start. Exposure to hypobaric hypoxia significantly increased lung wet weight and decreased femoral cortical thickness. Trabecular bone was spared from the detrimental effects of hypobaric hypoxia, although a trend towards reduced bone volume fraction was found at the L4 vertebral body. Treatment with acetazolamide did not have any negative skeletal effects, but could not mitigate the altitude-induced bone loss. Zoledronate was able to prevent the altitude-induced reduction in cortical thickness. In conclusion, simulated high altitude affected primarily cortical bone, whereas trabecular bone was spared. Only treatment with zoledronate prevented the altitude-induced cortical bone loss. The study provides preclinical support for future studies of zoledronate as a potential pharmacological countermeasure for altitude-related bone loss.